BUDAYA LOKAL DAN HEGEMONI NEGARA DALAM KELOMPOK BUDAYA MACAPATAN SEBAGAI SARANA LEGITIMASI POLITIK ORDE BARU - Suparlan Al Hakim (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: Discourse politics in socio-cultural and political analysis often raise debates. The debates come out in terms of the positioning of local culture products when they are communicated with the concepts of statesmanship/nationalism. In this case, it can bring a shift from a local culture concept to the political one. If it happens, the state tendency in controlling local cultures is bigger. It is due to the desire ofthe state/government to get its legitimacy and strengthen its hegemony latently. Theemergence of a local culture group